Interacciones empaque-alimento: migración (2014)
Foodstuffs quality and safety are important issues involving packaging behavior in food preparing and storing processes. In this context, food legislation compliance increasingly demanding, concerns the knowledge of several key aspects of food-packaging systems. This article presents a review about main packaging materials currently used in the food industry, their interactions with the packaged product, mainly migration of macro and microelements from packaging to food, analytical techniques and mathematical models used in elements migrants identification, the national and international regulations established.